AWARENESS OF INTRAORAL PHOTOGRAPHY AMONG DENTAL STUDENTS - Teja Maddula, Ravi; Abraham, Abby; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Precise shade matching is one of the most testing parts of dental restorations and stylish dentistry. Because of the incredible assortment of regular tooth shading, accomplishing a nearby shade match of a fake rebuilding with normal dentition is a mind-boggling process. Photography has been utilized for a long time trying to improve correspondence among dental specialists and dental professionals.The aim of the study was to evaluate the awareness of intraoral photography among dental graduates. This was a questionnaire-based cross-sectional type of study comprising 100 dental college students in Chennai. A self-designed questionnaire contains 10 questions based on the knowledge and awareness of intraoral photography among dental college students. Questionnaires were circulated through an online website survey planet.After the responses were received from 100 participants, data was collected and analysed.76% of dental graduates stated the intraoral photographs were taken in automatic mode, and only 24% of dental graduates set the camera in manual mode to capture the intraoral image. 97% of dental graduates use the grey card as a contrast to the subject taken, 98% of dental graduates are unaware about the use of white balance in camera settings, and 1% of dental graduates are only aware of the 18% grey card and the use of the gray card to pre-set the white balance. 100% of the people recommend the intraoral photography courses included in the dental course. 33% of the graduates have attended the photography courses to learn the technique to capture the intraoral photographs.The awareness of intraoral photography among dental students is moderately adequate. More than 30 of the graduates have attended the photography courses to learn the technique to capture the intraoral photographs. The documentation of the clinical cases is being encouraged in dental schools, but the proper training for the intraoral photographs is not being met. 100% of graduates recommend the photography courses be included in the dental curriculum.